ESTIMATE OF ENERGY EXPENDITURE IN PHYSICAL EDUCATION CLASSES FOR STUDENTS WITH DISABILITIES IN DIFFERENT SYSTEMS OF INTELLECTUAL EDUCATION. (Fiep Bulletin - online, 2011)
Introduction: Physical inactivity alone accounts annually for approximately two million deaths worldwide. Objective: To analyze the aspects related to body composition (BMI and WHR) and estimated energy expenditure in physical education classes in 11 to 13 years, male, owned by six public schools, four with the system of inclusion ( I) and 2 with the special education (EE), both in low-income Ceilândia City, Distrito Federal - Brazil. Methodology: A sample of 38 students, being 18 and 20 of inclusive education for special education were studied during a normal week of school physical education. In statistical procedures, descriptive study, we used the ANOVA and Scheffé test for comparisons between groups. Criteria established for p values
Keywords: Energy expenditure; Physical Education and School